MODERATION OF INTERNAL CONTROL SYSTEM IN THE RELATIONSHIP BETWEEN INTERNAL AUDITOR COMPETENCE AND ORGANIZATIONAL JUSTICE OF FRAUD PREVENTION - Kharie, Sitti Marwa; Darwis, Herman (Nominal: Barometer Riset Akuntansi dan Manajemen, 2020)
This research aimed to known the effect of internal auditor competence and the justice organization toward prevention of fraud with internal control system as moderate variable. The population of this research is Government Internal Controlling (APIP) in Inspektorat of North Moluccas. The method of taken sample is used multistage sampling. The technique which used to examine the hypotesa is simple regression and examine moderate variable used absolute difference value test.The result of this research is to show that internal auditor competence affect to prevention fraud justice organization is not affect to prevention fraud, internal control system can moderate internal auditor competence to prevention fraud, while the justice organization is not affect to prevention fraud which moderated by internal control system.